ELIMINASI RISIKO OPERASIONAL BMT SRI SEJAHTERA SURABAYA - Putra, Yanuar Dharma; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The results of this research are risk mitigation measures in the continuity of internal processes, human resources, technology and information. Risk mitigation on the internal processes is done by performing supervision based on employees job description, and implementation of sharia financing agreements with customers. Risk mitigation on human resources is done by providing moral guidance to employees. Risk mitigation in information technology is carried out by performing regular maintenance of computer software and hardware, as well as other devices that support Baitul Maal wa tamwil Sri Sejahtera business activities. REFFERENCES Alexander, Carol. 2003. Operational Risk: Regulation, Analysis and Management. London: Prentice Hall Alijoyo, Antonious. 2006. Enterprise Risk Management: Pendekatan Praktis. Edisikedua. Jakarta: PT. Ray Indonesia Chapra, M. Umer. 2000. Islam dan Tantangan Ekonomi. Jakarta: Gema Insani Press dan Tazkia Institute Djohanputro. Bramantyo. 2006. Prinsip-Prinsip Ekonomi Makro. Cetakan 1. Jakarta: PPM Frame. J. Davidson. 2003. Managing Risk in Organisations: A Guide for Managers. San Francisco. Jossey Bass: A wiley imprint Herman, Darmawi. 2008. Manajemen Risiko. Jakarta: Bumi Aksara Ilmi, Makhalul. 2002. Teori dan Praktek Lembaga Mikro Keuangan Syariah: Beberapa Permasalahan dan Alternatif Solusi. Yogyakarta: UII Press Karim, Adiwarman Azwar. 2006. Bank Islam: Analisis Fiqih dan Keuangan. Jakarta: PT. Raja Grafindo Persada Khan, Tariqullah and Habis Ahmed. 2008. Manajemen Risiko Lembaga Keuangan Syariah. Jakarta: Bumi Aksara Mamduh, M. Hanafi. 2009. Manajemen RIsiko. Yogyakarta: UPP STI Manajemen YKPN Mirakhor, Abbas dan Zainal Iqbal. 2007. Pengantar Keuangan Islam: Teori dan Praktik. Terjemahan oleh A.K. Anwar. 2008. Jakarta: Kencana Media Group Mughni, Abdul. 2005. Keuangan Mikro Islam dalam Upaya Pengentasan Masalah Sosial. www.takzia.ac.id, (diaksespada 26 Februari 2017) Muhammad. 2002. Manajemen Bank Syariah. Yogyakarta: UPP AMP YKPN Muhammad. 2004. Manajemen Dana Bank Syariah. Yogyakarta: Ekonisia Redja, George E. 2008. Principles of Risk Management and Insurances. Edisi ke-10. Boston: Pearson International Edition Sudarsono, Heri. 2004. Bank dan Lembaga Keuangan Syariah Deskripsi dan Ilustrasi. Yogyakarta: Ekonisia Sugiyono. 2015. Pendekatan Kuantitatif, Kualitatif, dan R&D. Cetakan Ke-21. Bandung: Alfabeta Suhendi, Hendi. 2009. Strategi Optimalisasi Peran BMTT sebagai Penggerak Sektor Usaha Mikro. www.fe.unpad.ac.id, (diakses pada 26 Februari 2017) Yin, K Robert. 2002. Studi Kasus (Desain dan Metode). Jakarta: PT. Raja Grafindo Persada Yin, K. Robert. 2009. Case Study Research: Design and Method (4thed.). California: Sage Publications, Inc. Yin, K. Robert. 2013. Studi Kasus (Desain dan Metode). Jakarta: PT. Raja Grafindo Persada